2010
DOI: 10.4021/wjon2010.06.220w
|View full text |Cite
|
Sign up to set email alerts
|

Phyllodes Tumors of the Breast: A Review of 26 Cases

Abstract: BackgroundPhyllodes tumors of the breast are rare and locally aggressive neoplasms. Our study aimed to report the experience of the Farhat Hached Hospital (Sousse, Tunisia) acquired during a 7-year period and to give an additional review of the available literature.MethodsThe authors analyzed retrospectively clinical, radiological, histopathological and therapeutic features as well as outcome in a series of 26 cases diagnosed as phyllodes tumors of the breast at the Pathology Department of Farhat Hached Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
1
7
1
Order By: Relevance
“…Previous studies indicated occurrence of phyllodes tumors during pregnancy or lactation as benign, borderline or malignant, and unilateral or bilateral in 14 cases. 1,416 The findings of the present case of benign phyllodes tumor with lactational changes is concurrent with a case described previously by Likhitmaskul et al 1 in a 36-year-old pregnant woman who underwent mastectomy 3 weeks postpartum. Generally, phyllodes tumor presents as a relatively circumscribed painless mass.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies indicated occurrence of phyllodes tumors during pregnancy or lactation as benign, borderline or malignant, and unilateral or bilateral in 14 cases. 1,416 The findings of the present case of benign phyllodes tumor with lactational changes is concurrent with a case described previously by Likhitmaskul et al 1 in a 36-year-old pregnant woman who underwent mastectomy 3 weeks postpartum. Generally, phyllodes tumor presents as a relatively circumscribed painless mass.…”
Section: Discussionsupporting
confidence: 90%
“…summary of case reports of Phyllodes tumor occurring during pregnancy/lactation 1,[4][5][6][7][8][9][10][11][12][13][14][15][16]. …”
mentioning
confidence: 99%
“…However, the surgical approach has been based on histological features, the tumor-to-mammary-gland ratio, and patient desire for breast preservation, indicating that recurrence risk is biased by an aggressive surgical approach relative to the differential risk of disease recurrence. Compromised resection margins have also been linked to local and distant recurrence [14][15][16][17]. However, these rates were lower in our study than in previous reports [2,3,8].…”
Section: Discussioncontrasting
confidence: 67%
“…On mammography, PTs are seen as well-circumscribed round or oval-shaped lobulated masses which on occasion could contain some calcifications [ 5 , 6 ]. On sonography, they appear as well-defined solid masses with heterogenous internal echos, with no posterior acoustic attenuation [ 7 ]. If a solid mass containing clefts or elongated fluid-filled spaces is seen on sonography, PT should be considered.…”
Section: Discussionmentioning
confidence: 99%